2021
DOI: 10.5435/jaaosglobal-d-21-00193
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating Surgical Skill Decay in Orthopaedics Using Virtual Simulation Learning

Abstract: Background: The COVID-19 pandemic has interrupted orthopaedic training structures for both surgeons and trainees. The concept of skill decay must be considered during inactivity of elective practice. The purpose of this study was to provide an evidence-based curriculum in association with immersive virtual reality (iVR) to prevent skill decay during periods of training cessation and beyond. Methods: A review of pertinent literature for orthopaedic surgi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…By optimizing quality and costs through improved skill transfer, learning efficiency, and proficiency-based metrics, Lohr et al demonstrated that IVR directly improves the value equation for all shareholders (healthcare systems, institutions, trainees, and patients). 8 Providing surgical refresher training and preoperative practice using IVR could reduce operative time and improve patient outcomes, thereby reducing morbidity and opportunity costs across the spectrum of shareholders. Copyright © 2022 JPOSNA® www.jposna.org…”
Section: Current Role Of Ivr Ar and Mr In Orthopaedic Education And T...mentioning
confidence: 99%
See 1 more Smart Citation
“…By optimizing quality and costs through improved skill transfer, learning efficiency, and proficiency-based metrics, Lohr et al demonstrated that IVR directly improves the value equation for all shareholders (healthcare systems, institutions, trainees, and patients). 8 Providing surgical refresher training and preoperative practice using IVR could reduce operative time and improve patient outcomes, thereby reducing morbidity and opportunity costs across the spectrum of shareholders. Copyright © 2022 JPOSNA® www.jposna.org…”
Section: Current Role Of Ivr Ar and Mr In Orthopaedic Education And T...mentioning
confidence: 99%
“…Lohre et al illustrated the learning capacities of traditional and IVR simulator teaching modalities using a "virtual ladder of orthopaedic learning" with an endpoint of trainee proficiency. 8 The authors provide an additional concrete example of an IVR curriculum that aligns with international graduate medical education formats, such as ACGME and Canadian Medical Education Directives for Specialists (CANMeds).…”
Section: Introductionmentioning
confidence: 99%
“…1 Traditionally simulation is performed in-person, however given the need to socially distance, virtual simulation has been proposed in various forms as an educational tool. [2][3][4][5][6] The purpose of the current study was to assess whether simulation could be delivered virtually. Since lectures were already being delivered virtually, the platform for virtual education was already present, but the addition of a virtual simulation session was novel.…”
Section: Introductionmentioning
confidence: 99%
“…Producing, using, and maintaining training resources can be costly expenditures with variable levels of published evidence supporting the obtainment of the intended skill acquisition and retention (Nousiainen et al 2016;Zendejas et al 2013). Recently, Immersive Virtual Reality (IVR) has demonstrated itself to be a disruptive technology for surgical education, due to its improved learning efficiency and ability to quantitatively measure learning outcomes, in both technical and cognitive skill domains for surgical trainees (Lohre, Bois, Pollock, et al 2020;Lohre, Morrey, and Goel 2020;Lohre, Wang, et al 2020;Lohre et al 2021a;Mao et al 2021). Current offerings have been developed to leverage the interactive and realistic experience of IVR, maximizing evidence-based cognitive and behavioral-science learning concepts.…”
Section: Introductionmentioning
confidence: 99%